2011
DOI: 10.1088/0004-637x/738/1/60
|View full text |Cite
|
Sign up to set email alerts
|

Binary Formation Mechanisms: Constraints From the Companion Mass Ratio Distribution

Abstract: We present a statistical comparison of the mass ratio distribution of companions, as observed in different multiplicity surveys, to the most recent estimate of the single-object mass function. The main goal of our analysis is to test whether or not the observed companion mass ratio distribution (CMRD) as a function of primary star mass and star formation environment is consistent with having been drawn from the field star initial mass function (IMF). We consider samples of companions for M dwarfs, solar-type s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 50 publications
6
80
0
Order By: Relevance
“…However, Reggiani & Meyer (2011) found an uncertainty on this power-law slope of dN dq ∼ q −0.5±0.29 . This implies that the observed mass ratio distribution is still consistent with being flat at the two sigma level.…”
Section: Flat Mass Ratio Distributionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, Reggiani & Meyer (2011) found an uncertainty on this power-law slope of dN dq ∼ q −0.5±0.29 . This implies that the observed mass ratio distribution is still consistent with being flat at the two sigma level.…”
Section: Flat Mass Ratio Distributionmentioning
confidence: 95%
“…For the period distribution we use the log-normal distribution with a mean period of 5.03 and a dispersion of 2.28 in log 10 days, which was found by Raghavan et al (2010). For the secondary to primary mass ratio (q) we use the power-law from Reggiani & Meyer (2011) of dN dq ∼ q −0.5 for 0.1 < q < 1. By setting the maximum q to one we make the assumption that the observed (brightest) star in a binary will always be the most massive one.…”
Section: Binary Propertiesmentioning
confidence: 99%
“…Concerning the mass-ratio distribution, we draw two masses randomly (in Model A) from the same single IMF in order to get the primary and the secondary masses; the approach adopted by Kroupa (1995a). For all other models (except Model D) we adopted a flat mass-ratio distribution (Reggiani & Meyer 2011), and the IMF used to obtain the mass for the primary had to adjusted (see Sect. 6.1) so that once the pairing is done we retrieve the single IMF from Chabrier (2005) presented above.…”
Section: Binary Propertiesmentioning
confidence: 99%
“…Nevertheless, recent studies of both the Galactic field (Raghavan et al 2010;Reggiani & Meyer 2011) and star forming regions (Kraus et al 2008(Kraus et al , 2011 indicate that, whereas there is no clear and unique best fit, a flat mass ratio distribution may be a better fit than a random pairing. Since this would result in a slightly smaller number of very low mass companions, we may expect the criterion on N 4 to be better fulfilled.…”
Section: Binary Pairing (Model B)mentioning
confidence: 99%
“…Several surveys in the past decades focused on the detection of stellar binaries with the purpose of characterizing the occurrence of companions and their mass distribution both in the field (e.g., Raghavan et al 2010;Janson et al 2012) and in star-forming regions (e.g., Patience et al 2002). Reggiani & Meyer (2013), in an update of Reggiani & Meyer (2011), have shown that in the field the CMRD is consistent with being universal, independent of primary mass and separation in the range covered by the observations, and can be fit by a single power-law slope dN/dq ∝ q β , with β = 0.25 ± 0.29. In addition, N-body simulations suggest that the CMRD is only modestly affected by dynamics, even in dense clusters, as opposed to the semimajor axis (SMA) distribution (Parker & Reggiani 2013).…”
Section: Introductionmentioning
confidence: 99%